Knowledge and Practice of Nurses in Preventing Ventilator Associated Pneumonia in the Pediatric Intensive Care Unit, Songklanagarind Hospital - ชูชาติ, วันดี; สายวารี, จริยา (Princess of Naradhiwas University Journal, 2018)
The purposes of this descriptive research were 1) to study the knowledge of nurses in preventing ventilator associated pneumonia 2) to study the practice of Nurses in preventing ventilator associated pneumonia, and 3) to examine the relationships between personal factors and the knowledge and practice of nurses in preventing ventilator associated pneumonia. The purposive sample consisted of 28 nurses who had worked in a Pediatric Intensive Care Unit at least 6 months and had passed their performance appraisal. Data were collected by three questionnaires on demographic data, knowledge and the practice of nurses in preventing ventilator associated pneumonia. Content validity index (CVI) was judged by three experts = 0.85. The statistical data analysis was conducted using descriptive statistics including percentage, mean, and standard deviation, inferential statistics by Chi Square test. The results of this study showed that 1) the knowledge of most nurses was at a high level (mean= 23.93, SD = 1.82); 2) the practice of most nurses was at a high level in every part (mean= 3.78, SD = 0.13); 3) There were no relationships between personal factors and the knowledge (P > 0.05) and the practice of nurses, since both were at a high level. Therefore the results of this study should be considered to improve continuous process of practice and quality of nursing care in preventing ventilator associated pneumonia.